Elimination of background in film-based applications - Rachael M. Berry; Stefan Schmitz; Brian D. Johnson; Boguslawa Dworecki; Elizabeth A. Fritz; Kenneth A. Roebuck; Kimberly K. Hines (BioTechniques)
Erase-It® Background Eliminator is a solution used directly on processed film to remove background or improve data resolution. Traditional methods, such as optimization of the scientific protocol or better estimation of exposure time, are tedious and uncertain. Nevertheless, autoradiography continues to be a simple, effective method to visualize data. Therefore, we evaluated the ability of Erase-It Working Solution to help solve background and resolution issues. To demonstrate the efficiency of the Background Eliminator, we analyzed the product's ability to remove signal evenly, performance on several brands of film, and usefulness with various detection methods. Even reduction of signal was demonstrated by performing densitometric analysis on film generated from a dot blot with serial dilutions of analyte. In addition, overexposed films from various suppliers were effectively treated to remove background and visualize data. Autoradiographs, generated with 32P-labeled probes, and chemiluminescent substrate were also processed resulting in clearer images. Our results demonstrate that film data can be treated quickly and conveniently without fear of artificial enhancement. We show the Background Eliminator to be a universal and timesaving tool to visualize results that otherwise may be difficult to interpret.